Ameliorative Wound Healing Potency of Koenimbine via Attenuation of Inflammatory Cytokines in Hyperglycemia-Induced Rodent Model - Xu, Jing; Wang, Fei; Zhang, Minjuan; Chen, Maoyuan; Zhao, Ke; Liu, Yang; Li, Dong (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Managing wounds in diabetic patients requires specialized approaches due to their unique healing challenges. Diabetic wounds, particularly Diabetic Foot Ulcers (DFUs), often exhibit delayed healing, increased infection risks and complications related to poor blood circulation, nerve damage and reduced immune function. Therefore, treating diabetic wounds represents a significant clinical and social concern, necessitating urgent research efforts to develop effective treatments that enhance wound healing across all dimensions. Materials and Methods: We investigated the bioactive compound koenimbine potency in promoting wound healing in a hyperglycemic rat model. Healthy Wistar rats were induced to have diabetes and then subjected to wound excision treatment. They were administered two different doses of koenimbine for a duration of 14 days. Glycemic and insulin levels were monitored throughout the treatment period with regular intervals. Wound diameter, percentage of wound closure, epithelization day, total collagen and protein content were measured to assess the impact of koenimbine administration of wound healing. Results: Free radical scavenging potency of the koenimbine on the diabetic wounds were also measured. Inflammation stimulating cytokines were quantified to evaluate the attenuating effect of koenimbine against hyperglycemia induced inflammation. The transcription factor NF-κB, known for promoting pro-inflammatory cytokines, along with the inflammatory mediators COX-2 and iNOS, as well as matrix metalloproteinases 2 and 9, which play a role in the degradation of extracellular matrix components, were measured to evaluate the signaling mechanisms by which koenimbine influences wound healing in diabetic rats. Koenimbine treatment effectively controlled glycemic levels and improved wound healing in diabetes-induced rats. It increased the antioxidant levels and reduced the inflammatory cytokines. Koenimbine administration inhibited the levels of NF-κB, COX-2, iNOS and MMP-2 and MMP-9, confirming its wound healing potency in diabetic rats. Conclusion: The positive impact of koenimbine was further demonstrated through our histopathological analysis of granulated wound tissue. Collectively, our findings indicate that koenimbine acts as an effective bioactive compound with the potential to enhance all three stages of diabetic wound healing.
Keywords: Diabetic wounds; Hyperglycemia; Impaired healing; Inflammation; Phyto drug; Koenimbine